(untitled) (GESTIÓN Y TENDENCIAS, 2018)
Leaseback is a financial contract used by companies to obtain liquidity from their fixed assets. In practice, a financial institution buys a company’s assets and then leases them back to that same company for a set period. This article presents a brief history of the first leaseback transaction carried out in Chile, in early 1980, as told by one of its protagonists.